Supernature : how Wilkinson Eyre made a hothouse cool - Keyte, Emma (ORO Editions, 2013)
"In 2012, Wilkinson Eyre was part of a British-led team that won the design competition for one of the most ambitious cultural projects of recent years—the masterplan for Singapore's Gardens by the Bay. One of the defining projects of this dynamic world city, the project set out to reinforce a vision of Singapore as a 'City in a Garden,' delivering a major visitor attraction and destination on the Marina Bay waterfront. The team—led by landscape architects Grant Associates—was subsequently commissioned to deliver the masterplan for the first phase of the gardens at Bay South, with Wilkinson Eyre leading the design of the key built element within them—the cooled conservatory complex. The conservatories cover an area in excess of 20,000 sq. m and are among the largest climate controlled glasshouses in the world, comprising a 1.28 hectare cool dry biome (the 'Flower Dome') and a 0.73 hectare cool moist biome (the 'Cloud Forest'). Together they represent a uniquely collaborative approach to design, bringing together scientific and design disciplines to meet the challenge of creating cool growing conditions in a building typology more frequently used to produce a warm environment for plants. Supernature tells Wilkinson Eyre's story of the design, describing in detail the challenges of designing and delivering this highly technical and culturally significant project, and following the team through the early conceptual design stages as well as the construction process. It also includes an architectural critique of the building and an essay placing the project in the context of Wilkinson Eyre Architects' wider portfolio."--Publisher's website.